Abundance and characteristics of microplastics in the surface water and sediment of parks in Xi'an city, Northwest China - Yu, Xiaoqin; Zhao, Yimo; Zhang, Chutian; Yang, Chengfang; Ouyang, Zhuozhi; Liu, Peng; Guo, Xuetao; Zhu, Lingyan (The Science of the total environment, 2022)
Microplastics (MPs), as a new type of pollutants, have attracted wide attention especially in recent years, but there was insufficient research on the distribution and characteristics of MPs in urban park water body. In this study, the pollution of MPs in water and sediment of Xi'an, the largest city in northwest China, was investigated. The MPs concentration in the surface water and sediment was 2900–6970 items/m3 and 940–3560 items/kg, respectively. According to the urban functions, the parks were divided into residential areas, commercial areas, tourism areas and industrial areas, and the highest abundance of MPs was observed in the tourism and residential areas, suggesting the impacts of human activities. MPs in these parks were mainly in four kinds of shapes, namely fiber, pellet, fragment and film, and dominated by fibers and fragments. Most of the extracted MPs were small in size, and 63–92% of them were smaller than 0.5 mm. Polypropylene and polyethylene terephthalate were the main polymer types in surface water and sediments, respectively. This study showed that the park water and sediment can be used as an important “sink” in MPs, which is of great significance for monitoring and alleviating the pollution of urban MPs. This study provided important reference for better understanding MPs levels in inland freshwaters. [Display omitted] •The microplastics in water and sediment of Xi'an Park were investigated.•PET and PP were the main polymer types of found microplastics.•Fibrous and small-sized (<0.5 mm) microplastics accounted for the majority.•The distribution of microplastics is influenced by human activities.